Tingkatan Makna Verba Prostitusi dalam Wacana Iklan Prostitusi Modern - Cicik Tri Jayanti (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: The meaning of prostitution is generally attached to sexual services around paid intercourse. However, the meaning of prostitution has expanded based on data about modern prostitution advertisements through Twitter social media. This research is a qualitative descriptive study that uses modern prostitution advertising discourse as data sourced from social media Twitter. Data collection was carried out from February 2 to March 15, 2021. After the data is collected, five steps are carried out, namely: (1) recording the verb prostitution, (2) writing down the abbreviation for the verb prostitution, (3) providing meaning, (4) finding the differentiating factor in the field of meaning, and (5) giving the level of the verb prostitution. Through matrix data analysis, 44 prostitution verbs have been graded based on eight different meaning factors, namely (1) Incall, (2) outcall, (3) Talking, (4) Laughing, (5) Relaxing, (6) Caring, (7) Ditemenin curhat, (8) Curhat, (9) Talk cutiepie, (10) Bacain dongeng sebelum tidur, (11) Deeptalk, (12) Healing, (13) Touching, (14) Nokiss, (15) Nosex, (16) Mutualisme, (17) Mutualan, (18) Pacar Kontrak, (19) GFE, (20) Professional cuddler, (21) Cuddle only, (22) hug, (23) Cuddle, (24) Pelukan, (25) Cuddling, (26) Cuddlecare, (27) Deephug, (28) Cudlle care, (29) Cc, (30) Sekadar dusel, (31) Sleeping, (32) Kissing, (33) FK, (34) foreplay, (35) HJ, (36) BJ, (37) Lc, (38) Love care, (39) LC berfantasi, (40) VCS, (41) SL, (42) HS, (43) Morning sex, dan (44) LT. The level of meaning is based on the order from the lightest meaning to the one with the most complex level of prostitution. Keywords: prostitution verbs, differentiators of meaning, levels of meaning, advertising discourse, modern prostitution advertisements. Abstrak: Makna prostitusi pada umumnya dilekatkan dengan layanan seksual seputar hubungan badan yang berbayar. Akan tetapi, makna prostitusi ternyata meluas berdasarkan data wacana iklan prostitusi modern melalui media sosial twitter. Penelitian ini merupakan penelitian deskripsi kualitatif yang menjadikan wacana iklan prostitusi modern sebagai data yang bersumber dari media sosial twitter. Pengambilan data dilakukan sejak 2 Februari hingga 15 Maret 2021. Setelah data dihimpun, dilaksanakan lima Langkah, yakni: (1) mencatat verba prostitusi, (2) menuliskan kepanjangan dari singkatan verba prostitusi, (3) memberikan pemaknaan, (4) menemukan faktor pembeda medan makna, dan (5) memberi tingkatan verba prostitusi. Melalui analisis data matrix, diperoleh 44 verba prostitusi yang telah digradasi berdasarkan delapan faktor pembeda makna, yakni (1) saluran, (2) lisan, (3) sentuhan, (4) interaksi, (5) pelukan, (6) rebahan, (7) bibir, dan (8) seksual. Adapun 44 verba prostitusi meliputi (1) Incall, (2) outcall, (3) Talking, (4) Laughing, (5) Relaxing, (6) Caring, (7) Ditemenin curhat, (8) Curhat, (9) Talk cutiepie, (10) Bacain dongeng sebelum tidur, (11) Deeptalk, (12) Healing, (13) Touching, (14) Nokiss, (15) Nosex, (16) Mutualisme, (17) Mutualan, (18) Pacar Kontrak, (19) GFE, (20) Professional cuddler, (21) Cuddle only, (22) hug, (23) Cuddle, (24) Pelukan, (25) Cuddling, (26) Cuddlecare, (27) Deephug, (28) Cudlle care, (29) Cc, (30) Sekadar dusel, (31) Sleeping, (32) Kissing, (33) FK, (34) foreplay, (35) HJ, (36) BJ, (37) Lc, (38) Love care, (39) LC berfantasi, (40) VCS, (41) SL, (42) HS, (43) Morning sex, dan (44) LT. Sementara kedelapan faktor pembeda makna mencakup (1) saluran, (2) lisan, (3) sentuhan, (4) interaksi, (5) pelukan, (6) rebahan, (7) bibir, dan (8) seksual. Tingkatan makna tersebut berdasarkan urutan dari makna yang paling ringan hingga yang memiliki tingkat prostitusi paling kompleks. Kata kunci: verba prostitusi, pembeda makna, tingkatan makna, wacana iklan, iklan prostitusi modern